Utilizing of aerial photography to study the distribution of seaweed in Saphan Hin Park, Mueang District, Phuket Province, Thailand - Kumlom, T.; Phewphan, U.; Ponganan, N.; Rakasachat, C. (International Journal of Agricultural Technology, 2025)
Seaweed is essential in ecosystems for producing oxygen and absorbing carbon dioxide, thereby reducing the greenhouse effect. It also provides habitat and food for various aquatic species and helps mitigate coastal erosion. The periodic surveys identified seaweed was done in four periods in January, April, August, and October covered the areas of 897.96 sq.km, 9,164.26 sq.km, 6,462.12 sq.km, and 14,678.95 sq.km, respectively. For Seaweed lumps, the areas were 30.12 sq.km, 310.54 sq.km, 903.28 sq.km, and 1,552.02 sq.km, respectively. The classification results were invaluable for effective natural resource planning and management. While the overall seaweed distribution remained stable, and some areas showed density changes. The resulting maps highlighted the advantages of using UAV aerial snapshots and MLC techniques for accurately identifying seaweed in shallow waters. The findings are anticipated to serve as a model for monitoring changes to support seaweed conservation and restoration and can be applied to other contexts involving natural resource and environmental management.